2021
DOI: 10.5194/acp-21-17495-2021
|View full text |Cite
|
Sign up to set email alerts
|

Eastward-propagating planetary waves in the polar middle atmosphere

Abstract: Abstract. According to Modern-Era Retrospective Research Analysis for Research and Applications (MERRA-2) temperature and wind datasets in 2019, this study presents the global variations in the eastward-propagating wavenumber 1 (E1), 2 (E2), 3 (E3) and 4 (E4) planetary waves (PWs) and their diagnostic results in the polar middle atmosphere. We clearly demonstrate the eastward wave modes exist during winter periods with westward background wind in both hemispheres. The maximum wave amplitudes in the Southern He… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…In addition, Tang et al. (2021) found that strong instability with weak background wind can promote the propagation and amplification of EP flux. The meridional and vertical components of EP flux refer to the flow of wave energy density and the EP flux gives details about the net effect on TPWs of eddy and momentum fluxes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Tang et al. (2021) found that strong instability with weak background wind can promote the propagation and amplification of EP flux. The meridional and vertical components of EP flux refer to the flow of wave energy density and the EP flux gives details about the net effect on TPWs of eddy and momentum fluxes.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, regions with a negative meridional gradient of the quasi-geostrophic potential vorticity (QGPV) indicate a higher probability of barotropic/baroclinic instabilities for generating PWs (Ma et al, 2022;Qin et al, 2021;Yamazaki & Matthias, 2019). In addition, Tang et al (2021) found that strong instability with weak background wind 5), and B on the right of A refers to the periods after the solstice (second half of B in Equation 5). can promote the propagation and amplification of EP flux.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, they found that the wave periods of W3 and W4 rise during the late summer in the Northern Hemisphere. Tang et al (2021) found the eastward wave in winter periods and westward background wind in both hemispheres. In addition, they observed that the mean phase speeds of zonal wavenumbers -1 (E1), -2 (E2), -3 (E3), and -4 (E4) were relatively stable, which are ~53 m/s, ~58 m/s, ~55 m/s, and ~52 m/s, respectively, at 70˚ latitude.…”
Section: Introductionmentioning
confidence: 87%
“…In addition, the short-term variation of migrating diurnal tides may be caused by the nonlinear interaction between tidal waves and Q2DWs (Chang et al, 2011). Gu et al (2021) found that W3 and W4 occurred more frequently around 48 h, while W2 tended to be short-period events. In addition, they found that the wave periods of W3 and W4 rise during the late summer in the Northern Hemisphere.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation